Engineered Cell Membrane-Derived Nanocarriers: The Enhanced Delivery System for Therapeutic Applications - Yu, Biao; Xue, Xu; Yin, Zhifeng; Cao, Liehu; Li, Mengmeng; Huang, Jianping (Frontiers in Cell and Developmental Biology, 2022)
There has been a rapid development of biomimetic platforms using cell membranes as nanocarriers to camouflage nanoparticles for enhancing bio-interfacial capabilities. Various sources of cell membranes have been explored for natural functions such as circulation and targeting effect. Biomedical applications of cell membranes-based delivery systems are expanding from cancer to multiple diseases. However, the natural properties of cell membranes are still far from achieving desired functions and effects as a nanocarrier platform for various diseases. To obtain multi-functionality and multitasking in complex biological systems, various functionalized modifications of cell membranes are being developed based on physical, chemical, and biological methods. Notably, many research opportunities have been initiated at the interface of multi-technologies and cell membranes, opening a promising frontier in therapeutic applications. Herein, the current exploration of natural cell membrane functionality, the design principles for engineered cell membrane-based delivery systems, and the disease applications are reviewed, with a special focus on the emerging strategies in engineering approaches.